2019
DOI: 10.20944/preprints201905.0044.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity Study of ANFIS Model Parameters to Predict the Pressure Gradient with Combined Input and Outputs Hydrodynamics Parameters in the Bubble Column Reactor

Abstract: Intelligent algorithms are recently used in the optimization process in chemical engineering and application of multiphase flows such as bubbling flow. This overview of modeling can be a great replacement with complex numerical methods or very time-consuming and disruptive measurement experimental process. In this study, we develop the ANFIS method for mapping inputs and outputs together and understand the behavior of the fluid flow from other output parameters of the bubble column reactor. Four inputs such as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 115 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…The operation of the turbines for the power potential and power demand constraints optimization using FL algorithm Selection of the number of units to optimize the energy generation Shamshirband et al [12] used an ANFIS and CFD approach to predict the pressure gradient. The investigation results indicated that the input parameters and the number of rules significantly influence the algorithm's accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The operation of the turbines for the power potential and power demand constraints optimization using FL algorithm Selection of the number of units to optimize the energy generation Shamshirband et al [12] used an ANFIS and CFD approach to predict the pressure gradient. The investigation results indicated that the input parameters and the number of rules significantly influence the algorithm's accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%